(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Beta thalassemia trait (BTT) is a common genetic disorder and a significant cause of microcytic anemia. Hemoglobin (Hb) electrophoresis is the gold standard for diagnosis, but its cost and availability are major concerns in resource-limited settings. The Mentzer index, a simple calculation using CBC parameters, has been proposed as a cost-effective alternative. Objective: To determine the diagnostic accuracy of the Mentzer index in identifying beta thalassemia trait using Hb electrophoresis as the gold standard. Methods: This cross-sectional validation study was conducted at the Department of Pediatrics, KRL Hospital, Islamabad over 6 months from September 2024 to February 2025. Children aged 4–16 years with Hb < 10.5 g/dL and MCV < 80 fL were enrolled. Mentzer index was calculated (MCV/RBC count), and Hb electrophoresis was performed. Diagnostic accuracy of Mentzer index < 13 was assessed against HbA2 > 3.5% on electrophoresis. Results: Among 242 children, the Mentzer index <13 showed a sensitivity of 92.5%, specificity of 87.2%, PPV of 90.2%, NPV of 89.2%, and overall accuracy of 90.2% in detecting beta thalassemia trait. Conclusion: The Mentzer index shows promising diagnostic potential in screening for beta thalassemia trait and may be used as a preliminary tool in settings where Hb electrophoresis is inaccessible or unaffordable.